'Reclaiming our time' in African Studies: conversations from the perspective of the Black Studies Movement in Germany. Issue 3 (1st September 2020) - Auma, Maureen Maisha; Otieno, Eric; Piesche, Peggy
Abstract : A group of scholars of African heritage convened in Berlin in December of 2017 to found a collective named 'Network for Black Perspectives in Research and Teaching'. One of its foundational tasks is to bridge the divide between Black Studies and African Studies in Germany. This text is one of the manifestations of this collective engagement. In a reflexive rather than normative exercise, our text explores how Black Studies scholarship and African Studies scholarship are impacted by the 'coloniality of knowledge and power' and by the 'violences of modernity'. We aim towards understanding our own entrapment, freedoms, complicity and solidarity as complex and layered realities. We draw on concepts of social cartography to conceptualize our embeddedness in the academy and to envision ways of navigating it in a decolonial mode. Borrowing from transnational decolonial scholarship, we attempt to map out the violent landscape we are faced with in African Studies and how we experience or endure harm in these spaces. We discuss four spaces of engagement, entrapment or reclamation within the wider institutional ecosystem of the University: The 'Everything is Awesome' space, the 'Soft-Reform' space, the 'Radical-Reform' space and the 'Beyond-Reform' space. Our collective text is generated from structured conversations around amplifying the voices of those who inhabit the shadow side of modernity in the context of transnational African Studies.